Effects of supplement and anthelmintic treatments on parasite establishment and performance of lambs artificially infected with Haemonchus contortus - Ginting, Simon P (Indonesian Animal Sciences Society, 1998)
The effect of feeding supplement and anthelmintic treatments on the establishment of parasites and the performances of lambs was studied in 24 St . Croix x Local Sumatra Crosses infected with Haemonchus contortus larvae (L3) . The study consisted of a 2 x 2 factorial arrangement involving two levels of supplement (1 .6% and 0.5% body weight ) and two levels of larval infection (0 and 3,000 L3 initial dose followed by a 1,000 L3-weekly dose) .The supplement x infection interaction was significant (P< 0.0001) on the egg counts and total serum proteins, but not on the PCV values (P>0.10) . The interaction was resulted from the shift in the magnitude of difference between supplement or between infection level and not by the shift in the rank between treatments . The 1 .6% body weight (BW) group had lower (P<0.0001) mean egg count than the 0.5% BW group (1,588 vs. 7,880) . Consistently, the blood PCV value and total serum proteins of lambs receiving 1 .6% BW supplement were higher (P<0.0001) than the 0.5% BW supplement group (28 .3 vs . 23 .8 and 5 .2 vs . 4.6, respectively) . Infection resulted in decreased feed and nitrogen (N) intake, but had no effect on fecal-N (P>0.0001). N-excretion (fecal-N + Urine-N) was not altered (P>0.10) by Haemonchus infection, but N-retention decreased in infected lambs due to a reduction in N intake . The effect of supplement and Haemonchus infection was significant (P<0.0001) on daily gain . Lambs on the 1 .6% BW supplement group grew faster than on the 0.5% BW supplement group whether they were infected or not . Infected lamb receiving 0.5% BW supplement lost weight during the experiment . It is concluded that an approach that combines the use of anthelmintics and supplement could ameliorate the influence of gastro-intestinal parasites on the performances of lambs, and reduces the intensity of using anthelmintics in controlling the parasites . Â Key words : Supplement, anthelmintics, Haemonchus contortus, lambs